IMPROVING STUDENTS' SPEECH ABILITY THROUGH A COMMUNICATIVE APPROACH TO LEARNING THE INDONESIAN LANGUAGE IN CLASS III ELEMENTARY SHOOL GMIM V TOMOHON - Mentiani, Ni Nyoman; Oentoe, Fientje; Tagupia, Juliana; Rorimpandey, Widdy H. F. (Journal of Educational Learning and Innovation (ELIa), 2023)
This study aims to improve students' speaking abilities through a communicative approach to learning the Indonesian language of third-grade students of GMIM V Tomohon Elementary School. The research problem formulation is how to improve speaking ability through a communicative approach of third-grade students of GMIM V Tomohon Elementary School. The subjects in this study were third-grade students of GMIM V Tomohon Elementary School with 21 students, while the object of this study was to improve students' speaking abilities through a communicative approach. This research was conducted in two cycles, and each cycle was conducted twice a meeting, so this class action research was successful. Based on the results of the study, it is known that improving students' speaking abilities through a communicative approach in learning Indonesian, from before the action, cycle I and cycle II. In cycle I action, it was known that seven students were complete or classical completeness only reached 60%. In cycle II, the completed students increased to 21 or a classical completeness of 87.61%. Thus, a communicative approach can improve students' speaking ability in learning Indonesian for third-grade students at GMIM V Tomohon Elementary School.